Insight Into Intellectual Property in Patent Medicine: An Indian Perspective - Murtala Ismail Adakawa; N S Harinarayana (Unnes Law Journal, 2022)
This paper aims at exploring intellectual property in relation to patent in medicine in India. Knowledge economy is the engine upon which development and creativity depends that has been instrumental in differentiating countries as developed or underdeveloped. India, being a member of World Trade Organization (WTO) has recognized the importance attached with IP thus investing hugely in intellectual advancement thereby reaping the advantages of second world population. Focusing on three key sectors namely, pharmaceutical, biotechnology, and IT sectors, scholars recognized the contributions these sectors offer to the growth domestic products and economic development of the countries. For instance, in India, many companies are continuously contributing to its economic development and growth at exponential rate. Many issues are discussed with regards to intellectual property.